2020
DOI: 10.1186/s40814-020-00649-3
|View full text |Cite
|
Sign up to set email alerts
|

A single-arm feasibility study of community-delivered Baduanjin (Qigong practice of the eight Brocades) training for frail older adults

Abstract: Background: Frailty is a common geriatric syndrome, characterized by reduced physiologic reserve and increased vulnerability to stressors, due to cumulative decline in multiple physiological systems. We studied the feasibility of a community-delivered Baduanjin (BDJ) training program among pre-frail/frail community-dwelling older people. We examined (1) safety (adverse events) and physical and psychological effects; and (2) feasibility of recruitment, retention, adherence; recruitment efforts, and any program … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 46 publications
2
13
0
Order By: Relevance
“…Our findings showed that the handgrip strength of the 12 week Baduanjin-based training group was significantly higher after the intervention, and also as compared with the control group at the post-intervention assessment. Our result was in accordance to that of Liu et al (29), who verified the positive effects of Baduanjin on handgrip strength, but, unlike our work, their study involved frail older adults and did not use comparisons with a control group, and to the study by Peng et al (30) in which they observed improvements in grip strength in the group that carried out a Baduanjin training for 12 weeks but in a sample of university students. In contrast, Tsai et al (31) found no statistically significant differences in grip strength of middle-aged women, after 8 weeks of another Chi Kung modality known as Ching Ching.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings showed that the handgrip strength of the 12 week Baduanjin-based training group was significantly higher after the intervention, and also as compared with the control group at the post-intervention assessment. Our result was in accordance to that of Liu et al (29), who verified the positive effects of Baduanjin on handgrip strength, but, unlike our work, their study involved frail older adults and did not use comparisons with a control group, and to the study by Peng et al (30) in which they observed improvements in grip strength in the group that carried out a Baduanjin training for 12 weeks but in a sample of university students. In contrast, Tsai et al (31) found no statistically significant differences in grip strength of middle-aged women, after 8 weeks of another Chi Kung modality known as Ching Ching.…”
Section: Discussionsupporting
confidence: 93%
“…Our evaluation included robust, pre-frail and frail individuals living in the community, which cannot be generalised to institutionalised older adults. While we adjusted for sex in all analyses, our study participants were mostly women, which is consistent with earlier studies showing that community exercise programmes attract mainly women [37][38][39]. Future studies should investigate the sex-specific effects on community-delivered pneumatic machine resistance training.…”
Section: Discussionsupporting
confidence: 78%
“…These findings highlight the importance of training specificity in older adults. In addition to resistance exercise, targeted training programmes for power, flexibility, balance and/ or endurance, can be complementary to mitigate other age-related physical or functional decline [37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Advancing age is also correlated with heart failure, pain symptoms, and mortality (Bell et al, 2015;Strand et al, 2018). As a result, there is a growing concern for older adults' health and well-being, which has led to an exploration of interventions to promote physical activity in this population (Liu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%